On Projective Systems of Rational Difference Equations - Palladino, Frank J. (Sarajevo Journal of Mathematics, 2024)
We discuss first order systems of rational difference equations which have the property that lines through the origin are mapped into lines through the origin. We call such systems projective systems of rational difference equations and we show a useful change of variables which helps us to understand the behavior in these cases. We include several examples to demonstrate the utility of this change of variables. 2000 Mathematics Subject Classification. 39A10,39A11